Culture in the communication age - Lull, James (London ; New York : Routledge, 2002)
Annotation What does it mean to live in the Communication Age? What has happened to culture in the Communication Age? What is the nature of culture today? Culture in the Communication Age brings together some of the world's leading thinkers from a range of academic disciplines to discuss what 'culture' means in the modern era. They describe key features of cultural life in the 'communication age', and consider the cultural implications of the rise of global communication, mass media, information technology, and popular culture. Individual chapters consider: * Cultures of the mind * Rethinking culture in a global context * Re-thinking Culture, from 'ways of life' to 'lifestyle' * Gender and Culture * Popular Culture and Media Spectacles * Visual Culture * Star Culture * Computers, the Internet and Virtual Cultures * Superculture in the Communication Age.
Culture of the mind : on the origins of meaning and emotion / Edward C. Stewart -- Rethinking the foundations of culture / Eduardo Neiva -- Thinking about culture in a global ecumene / Ulf Hannerz -- From ways of life to "lifestyle" rethinking culture as ideology and sensibility / David C. Chaney -- The question of cultural gender / Mirja Liikanen -- Cultural fronts : towards a dialogical understanding of contemporary cultures / Jorge A. Gonzalez -- Superculture for the communication age / James Lull -- Cultural the.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Culture; Communication and culture; Communication -- Social aspects; Culture; Culture; Communication et culture; culture note; culture (concept); Communication and culture; Communication -- Social aspects; Culture